Проблемы информационной экологии: украинские реалии - Шахова, Н.В. (Культура народов Причерноморья, 2013)
В работе рассматриваются негативные последствия информатизации в контексте
проблем информационной экологии, делается акцент на наиболее опасные тенденции развития
современного информационного пространства Украины. На конкретных примерах и
экспериментальном материале оценивается воздействие Интернета на молодое поколение украинцев,
предлагается ряд мер по обеспечению информационно-психологической безопасности личности. В роботі розглядаються негативні наслідки інформатизації в контексті проблем
інформаційної екології, робиться акцент на найбільш небезпечні тенденції розвитку сучасного
інформаційного простору України. На конкретних прикладах і експериментальному матеріалі
оцінюється вплив Інтернету на молоде покоління українців, пропонується низка заходів щодо
забезпечення інформаційно-психологічної безпеки особистості. At the present stage of development society volume of information has reached such proportions that
its impact on people can be considered a new factor in the environment, which requires adaptation of bio-social
personality. Awareness of the priority role of information and the dynamics of information activities suggest the
need for specific scientific field - information ecology. In this paper we consider the negative effects of
information in the context of the problems of information ecology, focuses on the most dangerous trends of
modern information space of Ukraine. This, above all, the promotion of moral values, contrary to the
traditional, their devaluation, the destruction of the ideology of the country.
Using specific examples, consider the Internet's impact on the young generation of Ukrainians; show, in
particular, which forms the image of a young Ukrainian advertising. We discuss the main results of the survey,
which measures the frequency of collisions students with dangerous web content, the nature and duration of stay
in the network, their view of safe work in Internet and the availability of parental controls.
Proposes a number of measures to provide information - psychological security of individuals - such as the need
to form information worldview, is to know the laws of functioning of media in society, understanding the essence
of information processes and the ability to withstand negative information influences.